The Hundred-Year Marathon : China's Secret Strategy to Replace America as the Global Superpower - Pillsbury, Michael (New York ST. Martin's Griffin, 2016)
"For more than forty years, the United States has reached out to China, helping it develop a booming economy and take its place on the world stage, in the belief that there is little to fear...and everything to gain...from China's rise. But what if the Chinese have had a different plan all along? The Hundred-Year Marathon reveals China's secret strategy to supplant the United States as the world's dominant power, and to do so by 2049, the one hundredth anniversary of the founding of the People's Republic. Michael Pillsbury, who has served in senior national security positions in the U.S. government since the days of Richard Nixon and Henry Kissinger, draws on Chinese documents, speeches, and books (many of them never translated into English) to reveal the roots of this strategy in traditional Chinese statecraft and track how the Chinese are putting it into practice today. Pillsbury shows how American policymakers have been willfully blind to these developments for decades...and he includes himself in that critique, as he was once a leading voice in favor of aiding China. He also calls for the United States to design a new, more competitive strategy toward China as it really is, and not as we might wish it to be. The Hundred-Year Marathon is a wakeup call for all Americans concerned about how we have misread the greatest national security challenge of the twenty-first century"
Include Notes and idnex
Keywords: United States -- China -- National security